Essentials of Marine Biotechnology - Kim, Se-Kwon.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This textbook introduces marine biotechnology by collecting the key knowledge on genetics, fish breeding, genetic diversity, seaweed production and microalgae biotechnology, and explores marine biomaterials and how they can benefit human health. Covering the latest applications of marine biotechnology in natural product development, genomics, transgenic technology, cosmeceuticals, nutraceuticals, and pharmaceutical development, it particularly focuses on future biological resources, developing functional materials from marine life, production of marine bioenergy and marine microbial resources and biotechnology. The author explains the structure of the book in an introductory note, and each chapter offers a detailed overview and conclusion to help readers better grasp the acquired knowledge. Lastly, the final part provides a comprehensive glossary with brief explanations of the key concepts in marine biotechnology. Written by a leading expert in the field withmore than 30 years of teaching experience, this book broadens students' understanding of the basics and recent developments in marine biotechnology.
What is Marine Biotechnology? -- Introduction to Molecular Biology -- Fish Genetics -- Fish Breeding and Biotechnology -- Genetic Diversity and DNA Markers in Fish -- Seaweed Biotechnology -- Microalgae, a Biological Resource for the Future -- Developing Functional Materials with Marine Organisms -- Marine Bioenergy Production -- Marine Natural Substances -- Marine Microorganism Resources and Biotechnology -- Index.
Keywords: Biotechnology; Genetics; Freshwater ecology; Marine ecology; Environmental chemistry; Analytical chemistry; Biotechnology; Genetics and Genomics; Freshwater and Marine Ecology; Environmental Chemistry; Analytical Chemistry